Efecto in vitro de siete fungicidas quimicos sobre beauveria baáiana (BALS.) Vuill. - Castellanos Gonzalez, L.=700 1 Muiño Garcia, B.L.; Lorenzo Nicao, M.E.; Rodriguez Fernandez, A.; Gomez Albernal, M.
(Es, En)
Ilus., 13 ref.
Keywords: FUNGICIDAS; HONGOS ENTOMOPATOGENOS; TOXICIDADA; BEAUVERIA BAáIANA; CUBA